The Structure and Properties of Microcrystalline and Submicrocrystalline Titanium Alloy VT1-0 in the Area of the Electron Beam Welding Seam - Klimenov V. A. Vasily Aleksandrovich; Gnyusov S. F. Sergey Fedorovich; Potekaev A. I. Aleksandr Ivanovich; Klopotov A. A. Anatoly Anatoljevich; Abzaev Yu. A. Yury Afanasjevich; Kurgan K. A. Kirill Andreevich; Marzol M. R. Mikhail Romualdovich; Galsanov S. V. Solbon Vladimirovich; Tsellermaer V. Ya. Vladimir Yakovlevich; Marchenko E. S. Ekaterina Sergeevna (2017, 2017)
Title screen